PENGARUH MAHASISWA KKN TERHADAP MOTIVASI DAN INSPIRASI MENGAJI ANAK DI MASJID NURUL FALAH DESA AIR PUTIH - Saputra, Azan Andika; Herianto , Satria; Amalia , Amanda Rosa; Karunia , Saryani; Ilhami , Putri Gusti; Desti , Diva; Pitri , Anisa; Rochmawati , Dina; Yulianto , Egik; Oktavia, Reza (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Air Putih Talang Empat Village, located in Central Bengkulu Regency, Bengkulu Province, is a village with characteristics reflecting rural life in Indonesia which is located at an altitude between 0-750 meters above sea level. Along the 100 meter incline road of Air Putih Village Hamlet I, in Air Putih, Talang Empat Sub-district, Central Bengkulu Regency, there are community service activities. The village road is the access for the people of Air Putih Village Hamlet I and II from the Air Sebakul highway. One of the most important components of village community welfare is the road, where various social activities interact with the residential environment. The aim is to show the extent to which social interaction affects the social condition of the community and the physical condition of the road. Air Putih Village in Talang Empat Sub-district, Bengkulu Tengah Regency has enormous potential in the agriculture and livestock sectors. However, the results of the initial survey and conversations with village officials as well as the local community indicate that the village has a number of problems that require special attention, namely the infrastructure to the place is not good, the mosque is under repair, the secretariat place for KKN, and environmental awareness is lacking. The purpose of this real work program (KKN) is to obtain feedback and input for the improvement of the higher education system of Fatmawati Sukarno Bengkulu State Islamic University (UINFAS) in harmony with the needs of the community, the direction of national development and the job market, helping the government accelerate the process of sustainable community development in various fields, especially the religious field and accelerating relations and synergizing UINFAS programs with government and society in order to obtain moral and material support for the existence and development of UINFAS in the future. The method of the KKN here is by observation, interviews and approaches with village officials, religious leaders, youth, and children. Based on the description above, the researcher is interested in conducting a project entitled the influence of KKN students on the motivation and inspiration of children's recitation at the Nurul Falah Mosque, Air Putih Village